Global patterns and climatic controls of belowground net carbon fixation - Gherardi, Laureano A.; Sala, Osvaldo E. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Carbon allocated underground through belowground net primary production represents the main input to soil organic carbon. This is of significant importance, because soil organic carbon is the third-largest carbon stock after oceanic and geological pools. However, drivers and controls of belowground productivity and the fraction of total carbon fixation allocated belowground remain uncertain. Here we estimate global belowground net primary productivity as the difference between satellite-based total net primary productivity and field observations of aboveground net primary production and assess climatic controls among biomes. On average, belowground carbon productivity is estimated as 24.7 Pg y−1, accounting for 46% of total terrestrial carbon fixation. Across biomes, belowground productivity increases with mean annual precipitation, although the rate of increase diminishes with increasing precipitation. The fraction of total net productivity allocated belowground exceeds 50% in a large fraction of terrestrial ecosystems and decreases from arid to humid ecosystems. This work adds to our understanding of the belowground carbon productivity response to climate change and provides a comprehensive global quantification of root/belowground productivity that will aid the budgeting and modeling of the global carbon cycle.